Frequency of Anosmia and Ageusia in COVID-19 Patients - Fatima Shahid , Nousheen Qureshi , Sundas Masood , Asmara Hussain , Memoona Afzal (Journal of Rawalpindi Medical College, 2021)
Background: With little research about the disease progress and its variants from asymptomatic individuals to patients suffering from type 2 respiratory failure, it has been a challenge to diagnose the affected individuals and control its spread. Different initial researches indicated presence of sudden anosmia and dysgeusia in asymptomatic or mild symptomatic carriers. Hence the purpose of my research was to find out the frequency of these symptoms in covid-19 positive patients. Methods: This is a retrospective study of 157 patients who were tested positive with COVID -19 between March and September 1, 2020. Because of restrictions on visits to clinics and hospitals and increased risk of exposure during the epidemic, patients were not examined. Data was collected through google forms and telephonic interviews of patients who suffered from covid 19 in the past. Results: The data was analyzed using spss version 23. According to our result ,of all the patients suffered from covid -19 58.1% patients presented with sudden onset anosmia and 53.8% presented with sudden hypogeusia without any previous history of such symptoms. Conclusion: The purpose of my research was to conclude frequency of symptoms of sudden onset anosmia and dysgeusia in COVID-19 patients in Pakistan. This will facilitate timely screening and thus isolation of affected individuals, thus decreasing the spread and lowering the curve. As proven, in addition of fever and sudden onset dry cough, isolated sudden onset anosmia(ISOA)should be considered one of the presenting complains.